Partisipasi Masyarakat Lokal dalam Pengembangan Agrowisata di Kebun Belimbing Tasikmadu Kecamatan Palang Kabupaten Tuban - Autika Pramesti Ayu Hadi Pratiwi; Nuriah Yuliati; Noor Rizkiyah (Departmen of Agribusiness, Economics and Management Faculty, Bogor Agricultural University, 2026)
Tasikmadu Starfruit Agrotourism has great potential but is not yet optimal in attracting tourists. The local government has formed a tourism awareness community group (POKDARWIS) to manage this agrotourism, but the results are not optimal compared to other tourism sectors in Tuban. This research aims to analyze the active participation of local communities in the management and development of agrotourism, analyze the quality standards for food safety, accommodation and other services and identify the condition of the Tasikmadu Tuban Starfruit Agrotourism infrastructure. The data analysis used was carried out through three objectives, namely community participation analysis, CBT (Community Based Tourism) analysis, and descriptive analysis. The research results show that community participation in the development of this agrotourism area shows varying levels. The urgency of this research lies in the aspect of active participation and the challenges faced both in terms of the economy and infrastructure conditions. New findings were made to provide efforts to deal with these problems by providing levels of community participation through 4 stages, namely Planning and Taking, Implementing, Monitoring and Evaluation and Utilizing and Enjoying the Results. Apart from that, this research also relies on the CBT (Community Based Tourist) concept as supporting success in developing agrotourism. It is hoped that this research will be able to provide solutions and insight into creating sustainable development of Tasikmadu Starfruit Agrotourism.